Coulomb stress transfer and accumulation on the Sagaing Fault, Myanmar, over the past 110 years and its implications for seismic hazard - Wei, Shengji (2018)
Myanmar is drawing rapidly increasing attention from the world for its seismic hazard. The Sagaing Fault (SF), an active right‐lateral strike‐slip fault passing through Myanmar, has been being the source of serious seismic damage of the country. Thus, awareness of seismic hazard assessment of this region is of pivotal significance by taking into account the interaction and migration of earthquakes with respect to time and space. We investigated a seismic series comprising10 earthquakes with M > 6.5 that occurred along the SF since 1906. The Coulomb failure stress modeling exhibits significant interactions among the earthquakes. After the 1906 earthquake, eight out of nine earthquakes occurred in the positively stress‐enhanced zone of the preceding earthquakes, verifying that the hypothesis of earthquake triggering is applicable on the SF. Moreover, we identified three visible positively stressed earthquake gaps on the central and southern SF, on which seismic hazard is increased.